STRATEGI KOMUNIKASI PERSUASIF HUMAN RESOURCES DEVELOPMENT DALAM MENYELESAIKAN KONFLIK KARYAWAN PT. DIMAS DRILLINDO CABANG DURI PROVINSI RIAU - Anaomi "; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Human resources development is a very peculiar position, he did not just pay attention to the environment in his department, but a duty pay attention and nurture all departments within the company's organizational structure. Drillindo Dimas companies especially those in the departments of human resouces development in addition to serving as security is concerned security in the company, which also runs the public relations function resolve employee conflicts. The purpose of the study is to examine the persuasive communication strategy development of human resources in resolving conflicts company employees Dimas Branch Drillindo Duri Riau province, as well as to determine the causes of conflict in the company Dimas Branch Drillindo Duri Riau Province.This research uses descriptive qualitative method is based on primary data source and secondary data and use the data collection techniques of observation, interviews, and documentation. Informants in the study as many as 7 people were determined by purposive sampling. Analysis using the model of interactive data analysis Miles and Huberman, where the data were obtained and processed to be reduced, so that the resulting presented a general conclusion, and examination techniques participation data using an extension that extends the participation of researchers to know the validity of the data.The results of this study indicate that persuasive communication strategies undertaken by human resources leadership development is very good. It is clear from the persuasive process conducted by the human resources leadership development can affect employees. Factors that are often the cause of conflict between employees is a communication error occurs between employees, lack of facilities owned by the company and other causes.Keywords: persuasive communication, conflicts, Human resources development.